Georeferenced 3D Laser Scanning Workflow for Enhanced As-Built Engineering Data - Umar Radzuan,; Hendy Fitrian Suhandri,; Sabil, Azmal; Muhamad Adli Faezal Rosnan,; Sarah Abdul Kareem Salih,; Muhammad Ismail Hassan,; Pandu Pradekso, (International Journal of Integrated Engineering, 2026)
Every built structure will endure a period of transformation over time, either due to natural deterioration or through intervention by renovation and preservation works. It is essential to record the building's current state by determining each component integrated with it, and this can be done by remodeling, referring to the dimensions of the building itself in the form of digital documentation. In common practice, the dimensions and data of the building are obtained by traditional measuring methods, where the process is time-consuming and may lead to errors. The objectives of these studies are to develop the workflow of built buildings' data documentation through 3D laser scanning with the aid of georeferencing to increase data accuracies. In the context of this study, the Student Centre located at Kampus Bandar, Universiti Tun Hussein Onn Malaysia, was chosen as the study area. The point clouds of the study area were documented and integrated with the georeferenced data, including three-dimensional coordinates (X, Y, and Z axis). As a result, it is ascertained that with the integration of georeferenced data on top of the point clouds, the outcome of the digital documentation will be more precise and accurate for future reference, specifically for design and construction works.  The results demonstrate that incorporating georeferencing data into to the point cloud data significantly improves the spatial accuracy and reliability of the resulting as-built data. Such enhanced datasets provide a dependable foundation for engineering applications, including design refinement, construction verification, and detailed structural assessment.